Roles and regulation of Aquaporin-3 in maintaining the gut health: an updated review - Zhu, Cui; Nie, Xiaoyan; Lu, Qi; Bai, Yinshan; Jiang, Zongyong (Frontiers in Physiology, 2023)
Aquaporin-3 (AQP3) is a predominant water channel protein expressed in the intestine, and plays important roles in the gut physiology and pathophysiology due to its permeability to water, glycerol and hydrogen peroxide. In this review, we systematically summarized the current understanding of the expression of AQP3 in the intestine of different species, and focused on the potential roles of AQP3 in water transport, different types of diarrhea and constipation, intestinal inflammation, intestinal barrier function, oxidative stress, and autophagy. These updated findings have supported that AQP3 may function as an important target in maintaining gut health of human and animals.